Ägyptologen und Ägyptologien zwischen Kaiserreich und Gründung der beiden deutschen Staaten : Reflexionen zur Geschichte und Episteme eines altertumswissenschaftlichen Fachs im 150. Jahr der Zeitschrift für Ägyptische Sprache und Altertumskunde - Bickel, Susanne, 1960-; Berg, Nicolas. (Zeitschrift für Ägyptische Sprache und Altertumskunde. Beiheft ;, 2013)
"The Journal for Egyptian Language and Ancient Studies (ZÄS) was first published in 1863, and this special volume celebrates the 150th anniversary of the oldest academic journal of Egyptology. Expert contributors present different aspects of the history of German Egyptology, the ZÄS, and important historical figures in the field. The volume covers the National Socialist period, and also includes essays on English, Belgian, and French Egyptology"--